Reference price effects in consumer choice for protein & impacts of subsidized pasture insurance on land value and use - Anderson, Andrew Emery (Kansas State University, 2023)
Essay 1: Consumers have faced rapidly changing food prices in recent years—meat prices have been particularly volatile—leading individuals to be frequently surprised by the prices they encounter. In contrast to neo-classical assumptions, applications of prospect theory to consumer choice have hypothesized that consumers evaluate prices relative to a reference price, are loss averse, and experience diminishing sensitivity. Accordingly, I tested for reference price effects in consumer choice for protein and demonstrated the implications in post-estimation analysis. I leveraged choice experiment data in a random utility framework while progressively incorporating various reference price features and found that including reference price effects improves model performance, both within and outside of the estimation sample. The magnitude of reference price effects varies by product and across marketing channels, with implications for elasticity estimates, market share predictions, and welfare analysis. My results are consistent with previous research but adds an application to a previously unstudied product group across market channels, while also demonstrating the implications of various modelling approaches. This additional information provides insights into protein markets and important guidance to researchers and policy analysts. Essay 2: Benefits of government subsidized farm programs may pass through the production sector to agricultural input prices. Likewise, publicly supported insurance programs can increase expected future revenue and reduce risk, thus altering production incentives and potentially impacting input prices and quantities. Accordingly, I examined the impact of Pasture, Rangeland, and Forage (PRF) Index Insurance on agricultural land values (price) and pastureland area (quantity). I leveraged the staggered rollout of PRF at the county level in a non-traditional Difference-in-Differences framework and found a positive effect on both farmland value and acres of pastureland. However, higher percentages of public land in a county are associated with smaller effects on land value and larger effects on pasture area. My results are in line with previous research and provide additional detail on the geographical impact. This additional nuance gives policy makers localized insights into the distribution of program effects.
Keywords: Reference price effects; Meat demand; Agricultural policy; Public land; Agricultural risk management